(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This theme explores the process of word formation and its fundamental characteristics. It delves into the various ways in which new words are created, including through affixation, compounding, blending, and conversion. The annotation also examines the role of morphology in word formation and the principles that govern the creation of new words in different languages. Additionally, it discusses the significance of word formation in language evolution and the impact of cultural and societal factors on the development of vocabulary. Overall, this theme provides a comprehensive understanding of the essential aspects of word formation and its implications for linguistic analysis.